Enhancing Elementary Numeracy Skills Through Visualization-Based Accelerated Learning Cycle - Hasibah Hasibah; Sama' Sama'; Jamilah Jamilah (STAI Hubbulwathan Duri, 2025)
Basic arithmetic skills are foundational for elementary education, yet many students struggle to grasp core mathematical concepts. Innovative teaching methods, such as visualization-based learning, may help address this issue by promoting conceptual understanding and critical thinking. This quasi-experimental study employed a Nonequivalent Control Group Design to evaluate the effectiveness of a visualization-based accelerated learning cycle on fourth-grade students’ arithmetic abilities. A purposive random sampling technique was used to assign 60 students into two groups: an experimental group (n = 30) and a control group (n = 30). Posttest results analyzed using a t-test indicated that the experimental group outperformed the control group, with an average score of 75.64 compared to 69.68. These findings suggest that visualization-based instruction can significantly enhance mathematical numeracy skills. The results demonstrate that visualization strategies support the acquisition of arithmetic concepts and foster critical thinking. The improved performance of the experimental group highlights the potential of this approach in elementary mathematics instruction. Visualization-based learning appears to be an effective method for improving arithmetic skills among elementary students. Its integration into classroom instruction could enhance learning outcomes, especially if supported by equitable access to technology. Future studies should investigate the long-term effects of this approach and include larger, more diverse samples.